Learning The Beautiful Month of Ramadan Based on The Project-Based Learning (PJBL) Model in Elementary School - Tri Kasih; Nuraini Nuraini (Universitas Tanjungpura, 2022)
This study aims to gain students' knowledge and understanding of the beautiful Ramadan. This study is a quantitative descriptive research approach. Classroom Action Research (CAR) is a way of determining how to do it with cycles. The sample was fourth grade students, totalling 28 students in elementary school. After cycle 1, 20 students passed with a percentage of 71%. Those who have not passed amounted to eight students with a percentage of 29%. Then we continued to Cycle II using the Project based learning (PjBL). At the end of cycle II, 28 students passed with a percentage of 100%.